1985
DOI: 10.1136/pgmj.61.716.501
|View full text |Cite
|
Sign up to set email alerts
|

Steroid sensitive systemic disease with anaemia in the elderly: a manifestation of giant cell arteritis?

Abstract: Summary Nine elderly patients presented with features of a multisystem disorder thought to be either a connective tissue disease of undefined type or disseminated malignancy. Associated features were a normochromic anaemia, raised erythrocyte sedimentation rate (ESR) (or plasma viscosity) and raised serum alkaline phosphatase levels. None had symptoms to suggest either giant cell arteritis or polymyalgia rheumatica. Temporal artery biopsy was performed before trial of corticosteroid therapy in f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1987
1987
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…Also, glucocorticoids can modulate arterial baroreceptor reflex control of renal sympathetic nerve activity (Scheuer and Mifflin, 2001;Bechtold and Scheuer, 2006). The previous reports indicated that the glucocorticoid treatment of superior cervical ganglia of rats at birth increased the SIF cells 10 times compared to untreated siblings (Allison and Gough, 1985). Consistently, Doupe et al (1985) reported that no SIF cells were observed after 3 weeks in culture in the absence of glucocorticoids confirming the vital requirement of GR on SIF cells.…”
Section: Discussionmentioning
confidence: 70%
“…Also, glucocorticoids can modulate arterial baroreceptor reflex control of renal sympathetic nerve activity (Scheuer and Mifflin, 2001;Bechtold and Scheuer, 2006). The previous reports indicated that the glucocorticoid treatment of superior cervical ganglia of rats at birth increased the SIF cells 10 times compared to untreated siblings (Allison and Gough, 1985). Consistently, Doupe et al (1985) reported that no SIF cells were observed after 3 weeks in culture in the absence of glucocorticoids confirming the vital requirement of GR on SIF cells.…”
Section: Discussionmentioning
confidence: 70%
“…Some elderly patients present with a significant normochromic, normocytic anaemia associated with elevated acute phase reactants. 58,59 These patients have no symptoms of PMR and no evidence of GCA but may represent a third manifestation of the same disease. 60 In parallel with the other two presentations, treatment with prednisone generally affords significant amelioration of this anaemia.…”
Section: A Review Of Research In Polymyalgia Rheumaticamentioning
confidence: 91%
“…1, 7,11,15 There is little evidence that the severity of the anaemia, which is generally considered to be the anaemia of chronic disease, has any prognostic significance for PMR although some exists in relation to GCA. 57,58 However, the anaemia may well define a third group of patients who may also be a part of the same clinical constellation as PMR and GCA. Some elderly patients present with a significant normochromic, normocytic anaemia associated with elevated acute phase reactants.…”
Section: A Review Of Research In Polymyalgia Rheumaticamentioning
confidence: 99%